Impact of image perceptibility in steganography - Phang, She Chin (2014)
This thesis discusses on the impact of image perceptibility in Image Steganography. By using the steganography to embed the secret message into the cover image. Method of the steganography will applied to the image perceptibility must be in either black and white or grey. The image of steganography generated must have visual quality same with the original version. Schemes of the steganography must be tested and make sure the changes on embedded image is not detect by naked eye from other. In this thesis, one of the steganography schemes for image of image perceptibility is proposed, Least Significant Bit (LSB) technique. LSB scheme will be uses to embed the secret message into a cover image. The result before and after embed the secret message should not produce an obvious different and detect easily by naked eye. So, it is considered as good image. In conclusion, schemes of the steganography will in effect the impact of image perceptibility to enhance security of the information and the concealment of information involve the sender and intended recipient only.